Immobilization of arsenic in tailing by using iron and hydrogen peroxide - Chung, IJ; Choi, YS; Hong, SW; Park, HM (SELPER LTD, PUBLICATIONS DIV, 2001)
Under environmental conditions, arsenic (As) reveals anionic behavior and is converted into various forms in accordance with the Eh/pH condition. This causes the difficulty of treating As with other heavy metals in tailing. This study was carried out to develop the immobilization method of arsenic in tailing as ferric arsenate (FeAsO4) using hydrogen peroxide. According to experimental results, the extracted concentrations of arsenic and iron (Fe) from tailing were reduced up to 84% and 93%, respectively. In the experiment using pure Pyrite (FeS2) and As solution, As concentration decreased with an increase of hydrogen peroxide dosage. The experimental results of re-extraction showed that only 10% of As and 20% of Fe were extracted in the case of using hydrogen peroxide. As a result, the long-term stability of this method was clarified.